Preparation of Silk Fibroin Nanoparticles and Enzyme-Entrapped Silk Fibroin Nanoparticles - Yu Zhang (Bio-Protocol, 2018)
After silk fiber is degummed in boiling 0.2% Na2CO3 solution, the degummed fibroin fiber could be dissolved in highly concentrated neutral salts such as CaCl2. The partially degraded polypeptides of silk fibroin, commonly called as regenerated liquid silk, could be obtained via water dialysis. The silk fibroin nanoparticles (SFNs) or enzyme-entrapped SFNs are prepared rapidly from the liquid silk by using acetone. The globular particles with a range of 35-125 nm in diameter, are water-insoluble but well dispersed and stable in aqueous solution. The nanoparticles are potentially useful in biomaterials such as cosmetics, anti-UV skincare products, and surface improving materials, especially in enzyme/drug delivery system as vehicle. Here, a detailed protocol for SFNs and enzyme-entrapped SFNs preparation is described.